Diffeomorphism type via aperiodicity in Reeb dynamics - Kwon, Myeonggi; Wiegand, Kevin; Zehmisch, Kai (Journal of fixed point theory and applications, 2022)
We characterise boundary-shaped disc-like neighbourhoods of certain isotropic submanifolds in terms of aperiodicity of Reeb flows. We prove uniqueness of homotopy and diffeomorphism type of such contact manifolds assuming non-existence of short periodic Reeb orbits.
Gesehen am 29.06.2022